Wage rigidities and old-age unemployment - Martin Kerndler; Michael Reiter (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
Aging populations have led many European countries to make an effort to increase the effective retirement age and keep workers longer in the labor force. An increase in the retirement age does not necessarily lead to a rise in the employment rate of older workers, as many could remain unemployed. In fact, the declining productivity of some older workers would require a wage cut for them to remain competitive. However, workers typically receive stable wages over their whole career, despite fluctuations in worker productivity: this 'wage smoothing' is an optimal feature of private employment contracts. The employment relation breaks up if the highest wage affordable by the firm is below the minimum wage acceptable for the worker. Conversely, wage rigidities - restrictions on individual wage setting such as a minimum wage, or market failures - can make separations bilaterally inefficient. This happens whenever the wage adjustment necessary to ensure continued employment either violates legal constraints or does not comply with individual incentives. How much of the empirically observed wage stability is explained by wage smoothing and how much by wage rigidities? Government intervention should focus on segments of the labor market where bilaterally inefficient separations due to wage rigidity are most likely, one of which is the labor market of older workers.
Keywords: 330; Lohnrigidität; Ältere Arbeitskräfte; Arbeitslosigkeit; Weiterbildung; Berufsbildungspolitik; Altersgrenze